2021
DOI: 10.1002/cnr2.1383
|View full text |Cite
|
Sign up to set email alerts
|

Ketogenic diet treatment in diffuse intrinsic pontine glioma in children: Retrospective analysis of feasibility, safety, and survival data

Abstract: Background: Diffuse intrinsic pontine glioma (DIPG) is one of the most devastating diseases among children with cancer, thus novel strategies are urgently needed.Aims: We retrospectively evaluated DIPG patients exposed to the carbohydrate restricted ketogenic diet (KD) with regard of feasibility, safety, and overall survival (OS).Methods and results: Searches of MEDLINE and Embase identified five hits meeting the search criteria (diagnosis of DIPG and exposure to KD). One additional case was identified by cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 31 publications
(68 reference statements)
0
17
0
Order By: Relevance
“…Weight loss was reported in studies by Rieger et al [ 8 ], Champ et al [ 16 ], Klein et al [ 29 ], and Panhans et al [ 28 ]. Vomiting was reported in the two studies by van der Louw et al [ 10 , 15 ], in the study by Panhans et al [ 28 ], and in that of Perez et al [ 27 ]. Nausea was reported in the studies by van der Louw et al, 2019b [ 15 ], Klein et al [ 29 ], and Panhans et al [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Weight loss was reported in studies by Rieger et al [ 8 ], Champ et al [ 16 ], Klein et al [ 29 ], and Panhans et al [ 28 ]. Vomiting was reported in the two studies by van der Louw et al [ 10 , 15 ], in the study by Panhans et al [ 28 ], and in that of Perez et al [ 27 ]. Nausea was reported in the studies by van der Louw et al, 2019b [ 15 ], Klein et al [ 29 ], and Panhans et al [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, these were not the only interventions applied. Drugs such as temozolomide, gemcitabine, prednisolone, bevacizumab, and lomustine were applied individually in four different studies (33.3%): temozolomide in the studies by van der Louw et al, 2019b [ 15 ] and Perez et al [ 27 ]; bevacizumab and lomustine in the study by Rieger et al [ 8 ]; lomustine in the study by Martin-McGill et al, 2018 [ 17 ]; and gemcitabine and prednisolone in the study by van der Louw 2019a [ 10 ]. In one study, patients received chemotherapy and concomitant radiotherapy as therapeutic interventions since the initial treatment with radiotherapy had no effect [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…efficacy against some cancers, clinical studies have been limited in glioma patients, and have so far mostly focused on feasibility, not outcomes [15,[21][22][23][24][25][26]. At the preclinical level, some studies showed that mice engrafted with IDH1 wt GBM did not benefit from KD [13,27], although others have suggested otherwise [28], and to the best of our knowledge, there has not yet been a direct experimental comparison of IDH1 wt and IDH1 mut gliomas exposed to KD.…”
Section: Plos Onementioning
confidence: 99%